Mapping the History of the State: The Historical Atlas of Maine - Hornsby, Stephen (Maine Policy Review, 2015)
This article describes the creation of the Historical Atlas of Maine, one of the most significant scholarly achievements in the humanities to come out of the University of Maine. Conceived in the late 1990s, the atlas was published by the University of Maine Press in 2015. It represents an enormously ambitious attempt to map the historical geography of the state from the end of the last ice age to the end of the millennium in 2000.